Perencanaan Strategis Sistem Informasi Menggunakan Framework TOGAF ADM Di Universitas Narotama Surabaya. - Bhisma Fajar Kusuma Putra; Made Kamisutara; Achmad Muchayan (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
Narotama University Surabaya faces challenges in integrating its academic information systems, which affect operational efficiency and the quality of learning services. This study aims to design an Enterprise Architecture (EA) using the TOGAF Architecture Development Method (ADM) as a strategic information system planning approach to support campus digital transformation. A qualitative descriptive method was employed, with data collected through interviews with eight key stakeholders, direct observation, and literature review. The findings indicate that major issues include data duplication, low system integration, and limitations in technology infrastructure. The proposed architecture design consists of integrated business, information system, and technology architectures. Furthermore, SWOT analysis is utilized to support implementation planning and architectural prioritization. The resulting Enterprise Architecture blueprint is expected to support the realization of an efficient, adaptive, and sustainable Smart Campus environment in line with Narotama University’s vision as a modern higher education institution driven by information technology.